Soil-transmitted Helminth Infection and Perinatal Outcomes in Pregnant Women in Primary Care Settings in South India: A Cohort Study - Revathi Ulaganeethi; Gowri Dorairajan; Nonika Rajkumari; Suganya Jayaraman; Sadhana Subramanian; Ganesh Kumar Saya (Wolters Kluwer Medknow Publications, 2024)
Background: Soil-transmitted helminth infections (STHs) in pregnancy have been linked to maternal anemia, low birth weight, and adverse perinatal outcomes. STH includes Ascaris lumbricoides, hookworm, and Trichuris trichiura. However, conflicting evidence exists regarding these effects. Hence, we aimed to assess the association of STH infections with perinatal outcomes. Methods and Materials: A community-based cohort study was conducted among pregnant women in primary care settings in Puducherry, South India, during December 2019 to April 2021. Stool samples were collected for STH screening and confirmed using polymerase chain reaction. Information on perinatal outcomes and hemoglobin levels were extracted from case records. The association of pre-term birth, low birth weight, anemia, and miscarriages with STH infection was analyzed using the Chi-square test. Results: Among the 650 women enrolled, 58 (8.9%) had one of the STH infections. At the time of recruitment, 336 (52.0%) women had anemia. Twenty-four women (3.7%) had miscarriages, 14 (2.2%) had pre-term birth, and 65 (10.4%) had low-birth-weight (LBW) babies. All 14 pre-term babies had LBW, and out of 65 LBW, 40 were in mothers with anemia. Incidence of LBW, pre-term deliveries, and anemia were higher in women with STH than in those without STH (LBW: 12.3% vs 10.2%, P = 0.62; pre-term: 3.5% vs 2.1%, P = 0.5; and anemia: 54.4% vs 51.85, P = 0.7). Conclusion: Though the incidence of anemia, LBW, and pre-term delivery was higher in women with STH infections compared to those without STH, we did not find any significant association between the presence of STH infections and perinatal outcomes.